Antigen density quantification of cell-surface immunotherapy targets by flow cytometry: Multi-antigen assay of neuroblastoma bone marrow metastasis - Molly T. Radosevich; Scott J. Bornheimer; Majid Mehrpouryan; Bita Sahaf; Jean S. Oak; Crystal L. Mackall; Sabine Heitzeneder (STAR Protocols, 2023)
Summary: The central role of target antigen density on chimeric antigen receptor T cell potency highlights the need for accurate measurement of antigen levels on clinical tumor samples. Here, we present a protocol for quantifying antigen density for six cell-surface antigens on neuroblastoma cells metastatic to bone marrow. We describe steps for patient sample acquisition, flow cytometry panel development, instrument setup, and compensation and detail procedures for running clinical samples and data analysis.For complete details on the use and execution of this protocol, please refer to Heitzeneder et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.